Metáfora e imaginação poética em Paul Ricoeur - Sanfelice, Vinicius Oliveira (2014)
This work intends to present the development of Ricoeur s theories of mimesis and representation, which he has built upon the concept of semantic innovation linked to metaphor. With Ricoeur, we followed the incorporation of Aristotle s mimesis ( bringingbefore- the-eyes ) and productive imagination (Kant s doctrine of schematism and free play concept) into the contemporary philosophy, drawing parallels with Husserl s phenomenology and with the analytic philosophy, through its lexicon (Wittgenstein s seeingas concept). We attempted to reassemble Ricoeur s theorization concerning the creation of poetic imagery and its practical importance to the redescription of reality and to art: the utopia and the creativity. In order to identify that creativity in Ricoeur s philosophy, we referred to the conflicts of opinion that surround metaphor, concept and imagination, pointing out the opposition between Derrida s ideas and Nietzsche s theory of intuitive metaphors (first metaphor) and presenting the cognitive aspects of poetic-creative imagination. The practical pertinence of this theory, as well as its aesthetic elements, is analyzed under the aegis of views of theorists who emphasized the formative role of imagination and metaphor (Jérome Cottin, Jean-Luc Amalric).